Literature Study: Optimization Strategy Of Rice Supply Chain Management In Regions - Putri, Anditania Sari Dwi (Program Studi Teknik Industri Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Efficient and sustainable rice supply chain management is essential to ensure the availability, quality, and price stability of rice in the regions. Factors that influence the efficiency of the rice supply chain include the quality of raw materials, logistics infrastructure, and coordination between farmers, distributors, government, and the private sector. Effective collaboration between related parties can increase productivity and distribution efficiency through the use of technology, strategic partnerships, and improvements in procurement and storage systems. However, the main challenges faced include dependence on weather, high costs, and issues of quality and sustainability of supply. Strategies implemented to overcome these challenges include improving infrastructure, diversifying technology, training for farmers, and strengthening the financing system that supports farmers. Further development is needed to strengthen the partnership between the private sector and the government, as well as introducing innovations in supply management to ensure the sustainability and efficiency of the rice supply chain in the future.